Difficulties in Differential Diagnosis of Post-Vaccination Period. Practical Examples - E. P. Nacharova; S. M. Kharit (Эпидемиология и вакцинопрофилактика)
Described four cases of illness in children hospitalized for one month after vaccination with live vaccines. In all cases the options considered in differential diagnosis between vaccinates reaction; undercurrents infections; separately shown the possibility of development of mumps in post-vaccination period vaccination party. The difficulties of differential diagnostics of diseases of post-vaccination period were analyzed. The necessity of laboratory examination in such cases to establish the etiological factor. The comparison of the system of registration of such events in the Russian Federation and abroad. The need to change the system of registration of adverse events in post-vaccination period.